Prevalence of untreated dental caries requiring endodontic therapy among rural and urban populations in India: A cross-sectional study - Kamil Shahnawaz (Bioinformation, 2026)
Dental caries is a major public health concern. If it is not treated in time, it can result into abscess and tooth loss. Therefore, it is of interest to determine and compare the frequency of unfilled caries that need root canal therapy among rural and urban adults in India. A cross-sectional study was carried out on 452 persons (226 rural, 226 urban). Clinical examination was done according to WHO oral health assessment criteria. Rural populations exhibit a higher burden of advanced dental caries requiring endodontic therapy, highlighting the need for targeted preventive and early intervention strategies.